(untitled) (Journal of Advanced Veterinary and Animal Research, 2015)
Peste des petits ruminants (PPR) is a highly contagious disease of domestic and wild small ruminants. Rapid and accurate laboratory assay are essential to enable the implementation of appropriate control strategies to restrict the spread of PPR. The present study was designed to detect the PPR virus (PPRV) antigen (N-gene) in nasal swabs and tissue samples. A total of 195 samples comprising of 138 nasal swabs from PPR suspected sheep (n=72) and goats (n=66), and 57 tissue samples comprising of lymph nodes from dead sheep (n=39) and goats (n=18) were collected from certain parts of Andhra Pradesh. The samples were subjected to sandwich-ELISA followed by RT-PCR for confirmatory diagnosis. In this study, PPRV could be detected in 27.53% (n=38/138) nasal swabs and 49.12% (n=28/57) tissue samples. Data showed that PPRV infection is widespread in the Andhra Pradesh, India. http://dx.doi.org/10.5455/javar.2015.b71